THE EFFECT OF PROFITABILITY AND FIRM SIZE ON CAPITAL STRUCTURE - Susanti, Susanti; Widyawati, Dini; Iswara, Ulfah Setia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
This study aims to examine the effect of profitability and firm size on the company's capital structure. This research was conducted on 209 observation listed on the Indonesia Stock Exchange. This research is classified as a quantitative research. The research data used is in the form of information on financial report data and annual reports of manufacturing companies listed on the Indonesia Stock Exchange in the period 2017 to 2021. The data analysis technique uses multiple linear regression analysis. In assessing the company's capital structure using the Debt to Equity Ratio, profitability using the Return on Assets ratio and company size using the log of total assets. The results showed that profitability had a significant negative effect on capital structure. Companies that are able to generate profits in their operational activities will use retained earnings rather than increasing the company's debt. Meanwhile, firm size has a significant positive effect on capital structure. This shows that the larger the size of the company, the greater the operational needs of companies whose funding can come from debt.